Species richness of beetle (Hexapoda: Coleoptera) in Suranadi Nature Recreation Park, Lombok Island - Mohammad Liwa Ilhamdi; Agil Al Idrus; Muhammad Syazali; Ahmad Raksun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aimed to determine the species richness of Hexapoda: Coleoptera in Suranadi Nature Recreation Park (NRP), Lombok Island, Indonesia. It is an exploratory, descriptive study with a qualitative method. Sample collection was carried out during May Ã¢â¬â July 2019 in three different habitats consisting of waterways along with the middle and edges of the forest. Sample collection was conducted using the pitfall trap method. The samples were identified at Biology Laboratory, Faculty of Teacher Training and Education, University of Mataram to obtain the species richness data. It was revealed that there were 11 species from 8 families of the Order Coleoptera. The species are Agonum micans, Trycorinus rudepunctatus, Euspilotus assimilis, Paracymus subcupreus, Phanaeus vindex, Myrmex sp., Dinopelma leptaleum, Oxyporus maxillosus, Oxylobus maridionalis, Tachys blandus and Platydema violacea.